Proposals for government credit allocation - Yeager, Leland B. (Washington : American Enterprise Institute for Public Policy Research, 1977)
The book examines congressional bills and other proposals for steering credit toward uses of supposed high social priority and away from low priority uses.
Includes bibliographical references.
usc 01/02/2019
Loans
Keywords: Credit control; United States